Classification of complications of epilepsy surgery and invasive diagnostic procedures: A proposed protocol and feasibility study. (18th August 2021) - Bjellvi, Johan; Cross, J. Helen; Gogou, Maria; Leclercq, Mathilde; Rheims, Sylvain; Ryvlin, Philippe; Sperling, Michael R.; Rydenhag, Bertil; Malmgren, Kristina
Abstract: Objective: In epilepsy surgery, which aims to treat seizures and thereby to improve the lives of persons with drug‐resistant epilepsy, the chances of attaining seizure relief must be carefully weighed against the risks of complications and expected adverse events. The interpretation of data regarding complications of epilepsy surgery and invasive diagnostic procedures is hampered by a lack of uniform definitions and method of data collection. Methods: Based on a review of previous definitions and classifications of complications, we developed a proposal for a new classification. This proposal was then subject to revisions after expert opinion within E‐pilepsy, an EU‐funded European pilot network of reference centers in refractory epilepsy and epilepsy surgery, later incorporated into the ERN (European Reference Network) EpiCARE. This version was discussed with recognized experts, and a final protocol was agreed to after further revision. The final protocol was evaluated in practical use over 1 year in three of the participating centers. One hundred seventy‐four consecutive procedures were included with 35 reported complications. Results: This report presents a multidimensional classification of complications in epilepsy surgery and invasive diagnostic procedures, where complications are characterized in terms of their immediate effects, resulting permanent symptoms, and consequences on activities of daily living. Significance: We propose that the protocol will be helpful in the work to promote safety in epilepsy surgery and for future studies designed to identify risk factors for complications. Further work is needed to address the reporting of outcomes as regards neuropsychological function, activities of daily living, and quality of life.